The protective effect of Gentiana lutea flower against mycotoxin toxicity in a gastrointestinal barrier in vitro model - Di Matteo, Giacomo; Frangiamone, Massimo; Vila-Donat, Pilar; Di Cecco, Valter; Di Martino, Luciano; Manyes, Lara; Mannina, Luisa (Frontiers in Nutrition, 2025)
ObjectiveWe investigated the phytochemical composition, gastrointestinal bioaccessibility, and protective effects against mycotoxin-induced toxicity of Gentiana lutea L. flower, a botanical species traditionally used in European herbal medicine.MethodsGentiana lutea flower samples were collected from the Majella National Park and chemically characterized using HPLC-PDA and NMR metabolomics, revealing the presence of abundant bioactive compounds (iridoids, secoiridoids, and xanthones), as well as quantifying the levels of amino acids, organic acids, and sugars. Following in vitro gastrointestinal digestion, bioaccessible fractions were analyzed and subjected to transepithelial transport assays using differentiated Caco-2 monolayers.ResultsGene expression analysis and cytotoxicity evaluation on Caco-2 cell cultures demonstrated that digested Gentiana significantly mitigated the toxic effects of aflatoxin B1 (AFB1), ochratoxin A (OTA), and beauvericin (BEA). The digested Gentiana samples reduced the expression of pro-apoptotic genes (BAX, CASP3), preserved intestinal barrier integrity by modulating tight junction-related genes (CL-2, ZO-1), and promoted antioxidant responses through SRXN1 regulation.ConclusionThese findings highlight the potential of Gentiana lutea flowers as a source of functional phytocompounds for intestinal barrier protection against mycotoxins.